Rancang Bangun Sistem Informasi Kerja Praktek Berbasis Web Pada Jurusan Teknik Elektro Universitas Riau - Dewi, Santi Aulia; Nasution, Salhazan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Job Training is one of the graduation requirements for students majoring in Electrical Engineering, University of Riau. The intended purpose of implementing job training is as a means for students todevelop skills and knowledge in accordance with their field of concentration. The job training system in the Electrical Engineering department at the University of Riau still has several weaknesses. Some of them are the use of google forms when students submit job training, the uneven amount of guidance for supervisors and the difficulty of conducting face-to-face guidance. The solution to these problems is to build a web-based job training information system that is used to manage job training data. The system is developed using the CodeIgniter web framework with PHP and HTML programming language. System testing use Black Box Testing and Usability Testing (USE Questionnaire and Likert scale).Keywords: Web, Job Training, Black Box Testing, Usability Testing, Codeigniter, USE Questionnaire.